Sounding Human with Data: The Role of Embodied Conceptual Metaphors and Aesthetics in Representing and Exploring Data Sets - Roddy, Stephen (My University, 2016)
Auditory display is the use of sound to present information to a listener. Sonification is a particular type of auditory display technique in which data is mapped to non-speech sound to communicate information about its source to a listener. Sonification generally aims to leverage the temporal and frequency resolution of the human ear and is a useful technique for representing data that cannot be represented by visual means alone. Taking this perspective as our point of departure, we believe that sonification may benefit from being informed by aesthetic explorations and academic developments within the wider fields of music technology, electronic music and sonic arts. In this paper, we will seek to explore areas of common ground between sonification and electronic music/sonic arts using unifying frameworks derived from musical aesthetics and embodied cognitive science (Kendall, 2014; Lakoff & Johnson, 1999).
the Proceedings of the Music Technology Workshop 2016
Music Technology Workshop
Keywords: Sonificiation; Embodied cognition; Aesthetics; Auditory display; Music composition; Creative Arts Practice; Creative Technologies; Digital Engagement; Digital Humanities; Smart & Sustainable Planet; Telecommunications; Auditory Cognition; Auditory Display; COGNITION; Computer Interface; Human-Computer Interaction; MUSIC; SOUND; Sonification; Sound Engineering; Community; Culture; History